Automated post-hoc noise cancellation tool for audio recordings acquired in an MRI scanner - Cusack, Rhodri; Cumming, Nick; Bor, Daniel; Norris, Dennis; Lyzenga, Johannes (Human brain mapping, 2005)
There are several types of experiment in which it is useful to have subjects speak overtly in a magnetic resonance imaging (MRI) scanner, including those studying the articulatory apparatus and the neural basis of speech production, and fMRI experiments in which speech is used as a response modality. Although it is relatively easy to record sound from the bore, it can be difficult to hear the speech over the very loud acoustic noise from the scanner. This is particularly a problem during echo‐planar imaging, which is usually used for fMRI. We present a post‐hoc sound cancellation algorithm, and describe a Windows‐based tool that implements it. The tool is fast and operates with minimal user intervention. We evaluate cancellation performance in terms of the improvement in signal‐to‐noise ratio, and investigate the effect of the recording medium. A substantial improvement in audibility was obtained. Hum. Brain Mapping 24:299–304, 2005. © 2005 Crown Copyright